Inventory Assessment Innovation in Teaching Speaking Skills Islamic Junior High School - Yusril Muhammad Nur; R. Umi Baroroh; Islam Youssry Elhadky (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2024)
This research aimed to innovate inventory assessment and carry out updates in inventory assessment instruments. This research used a "research and development" approach. As for the results of this research, researcher found the latest innovation in assessing Arabic language learning, especially at Maharah Kalam, namely by providing inventory assessment instruments to class VIII students at MTs Al Fath Klaten. In this inventory assessment, the researcher provides an assessment instrument in the form of a rubric. This rubric assessment instrument contains assessments in terms of the aspects being assessed, starting from the conformity of pronunciation, fluency and fluency with teacher standards, qowaid, intonation and language, accuracy of answers, courage to express opinions and mufrodat.